Introducing the ancient Greeks from bronze age seafarers to navigators of the western mind - Hall, Edith 1959- (New York W. W. Norton and Company, 2014)
Examines the ancient Greeks, from the rise of the Mycenaean kingdoms to the victory of Christianity over paganism, focusing on the qualities that characterized the widely diffused Mediterranean people over the long course of their history.
Seafaring Mycenaeans -- The creation of Greece -- Frogs and dolphins round the pond -- Inquiring Ionians -- The open society of Athens -- Spartan inscrutability -- Rivalrous Macedonians -- God-kings and libraries -- Greek minds and Roman power -- Pagan Greeks and Christians.
Includes bibliographical references (pages 279-287) and index.
Keywords: Greece -- History -- To 146 B.C.; Greece -- History -- 146 B.C.-323 A.D.; Greece -- Civilization -- To 146 B.C.